Evaluation of the Modified Jebsen Test of Hand Function and the University of Maryland Arm Questionnaire for Stroke. - Bovend'Eerdt, T; Dawes, H; Johansen-Berg, H; Wade, D (2004)
OBJECTIVE: To examine the concurrent validity and test-retest reliability of the Modified Jebsen Test of Hand Function (MJT) and the University of Maryland Arm Questionnaire for Stroke (UMAQS). DESIGN: Individuals with acquired neurological disorders were retested within an average of 9.6 days after the first assessment. SETTING: Individuals were recruited from two specialist rehabilitation units, members of the Multiple Sclerosis Society and Headway Group. SUBJECTS: Twenty-six individuals with acquired neurological disorders; stroke (12), MS (7), head injury (4), tumour (3) with moderate to high functioning upper limbs were recruited for this study. MAIN OUTCOME MEASURES: Arm function was assessed using the MJT, the UMAQS, the Nine Hole Peg Test (NHPT) and grip strength, calculating the ratio between affected and unaffected arm. RESULTS: The MJT showed good concurrent validity. Pearson's correlation with the NHPT was 0.86 and 0.88, on T1 and T2 respectively. The UMAQS showed no significant correlation with grip strength, the NHPT and the MJT. Test-retest reliability of the MJT was high with a correlation of 0.95, and 95% limits of agreement of 0.02 +/- 0.14. Correlations over time of the dominant hand/nondominant hand of the UMAQS were 0.72 and 0.83, with limits of agreement of -2.92 +/- 13.28 and 1.73 +/- 11.53. CONCLUSIONS: The present study supports the use of the MJT as a measure of gross functional dexterity. More information is needed to evaluate the UMAQS.